STRENGTHENING SCIENTIFIC PUBLICATION LITERACY THROUGH PREDATORY JOURNAL DETECTION TRAINING FOR GEOGRAPHY EDUCATION STUDENTS AT NUSA CENDANA UNIVERSITY - Martina Ayu Sejati; Poppy Haryani; Tugma Jaya Manalu; Sukmawati Sukmawati; Sunimbar Sunimbar (LPPM Univ. Ibn Khaldun Bogor, 2026)
Scientific publication literacy is a crucial competency for students completing their final research projects, yet many remain unfamiliar with predatory journals and proper journal submission procedures. This community service activity was conducted at the Geography Education Study Program, Nusa Cendana University, targeting 103 sixth-semester and final-semester students who were actively writing their theses. A preliminary survey revealed that 68 out of 103 participants did not know how to verify journal credibility or understand the stages of journal submission, both nationally and internationally. To address this, a structured training was conducted focusing on predatory journal detection, national journal classification under the Sinta 1 to 6 indexing system, and the complete journal submission process from manuscript preparation to publication. Following the training, post-test results showed that approximately 85 participants were able to distinguish predatory journals from legitimate ones, understand the journal submission stages, and differentiate between national and international journal categories. These results demonstrate that targeted training significantly improved students' scientific publication literacy and prepared them to make informed decisions when selecting journals for publishing their research findings.